Enunciação e linguagem: um estudo sobre a escrita do sujeito autista. - Braga, Flaviana Bezerra Pinheiro (2024)
Autism Spectrum Disorder (ASO) is a neurodevelopmental disorder present from birth or early childhood, which, as it is a spectrum, can manifest itself in different ways and intensity in individuais. ln general, oral language impairment ranges from persistence on specific subjects or difficulty in maintaining a dialogue to mutism and echolalia. Studies on written language and autism are still few when compared to oral language. The general objective of this research is to analyze the process of acquiring writing and its relationship with the subject, considering the uniqueness of the autistic child. For this, we had the specific objectives of examining the enunciative marks in the autistic subject's writing and analyzing whether there are specificities that characterize the process of writing acquisition in autism. We presentas a theoretical framework the linguistic-enunciative studies of Émile Benveniste (2022) and their developments in the research of Endruweit (2004; 2006; 201O), Silva and Endruweit (2011) and Flores (2018) to address the acquisition of writing and enunciation, building, from these studies, a path within the autism clinic. This is a qualitative and longitudinal case study type research, carried out based on the writing of a 9-year old child, diagnosed with Autism, levei 1 of support and undergoing psychopedagogical monitoring, a 3rd year student at a school particular to the municipality of Fortaleza, in the state of Ceará. For eight months, psychopedagogical monitoring was carried out at the clinic, carried out in weekly 40 minutes sessions, to collect data on children's writing, through photos and video recordings, which were later analyzed following Benvenist's enunciative guidelines. At the end of the analyzes we observed specificities in the autistic child's writing acquisition process, which configured a unique relationship between the subject. The specificities do not concern the characteristics of writing treated in the psychogenesis of writing, but the subject's late involvement with the written form of language, characterized by escapes from the written theme and the persistence in not recording the full proper name. With our findings, we seek to contribute to a pedagogy that values not only language, but language and its most varied manifestations. So that we can include the autistic child in the process of acquiring written language, after all, the environment provides the linguistic stimuli and the child provides the answers.